NILAI EKONOMI PEMANFAATAN KAWASAN KONSERVASI BAGI MASYARAKAT SEKITAR RESORT BODOGOL, TAMAN NASIONAL GUNUNG GEDE PANGRANGO - Oktania Kusuma Handayani; Nyoto Santoso; Tutut Sunarminto (Media Konservasi, 2015)
The utilization of the conservation area by the society in buffer area of Bodogol Resort done since the area was managed by Perum Perhutani. This research conducted to identify model of area utilization, economy value from the utilization and measure their dependence level communities to TNGGP. This research had done in Pasir Buncir and Wates Jaya village, Bodogol Resort, TNGGP on September until October 2014 by using the method Focussed Group Discussion (FGD), interview, questioner and observation.  Data analyze with qualitative descriptive. The result showed area usage model are contain by agriculture, plantation activities, and taking forest products. The usage conducted by 89% of local society. Total economy value from utilizing the surround on Pasir Buncir village is around Rp 145,392,000.00/year and Wates Jaya around Rp 249,667,333.00/year. Villager on Pasir Buncir and Wates Jaya still depend with Bodogol Resort area, which have been dependable value around 26.2% that show dependable needed for forest. Keyword: area utilization, Bodogol Resort, economy value